2007
DOI: 10.5194/angeo-25-2479-2007
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and seasonal variability of gravity-wave energy in the South-West Indian Ocean

Abstract: Abstract. Vertical temperature profiles obtained by radiosonde and Raman lidar measurements are used to investigate a climatology of total energy density of gravity waves (GW) in the Upper Troposphere (UT) and the Lower Stratosphere (LS) from 1992 to 2004 above Mahé (4 • S, 55 • E), Tromelin (15 • S, 54 • E) and La Réunion (21 • S, 55 • E) located in the tropical South-West Indian Ocean. The commonly used spectral index value (p≈5/3) of the intrinsic frequency spectrum is used for calculating estimated total e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Vertical profiles of temperature and horizontal wind with 100 m resolution reached the mean altitude of 23 km. Radiosonde data quality and accuracy are described in Chane Ming et al ( , 2007 and Ibrahim (2010), which used similar vertical profiles to characterize GWs in the UT/LS. At Ivato airport (389 m altitude), 40 GPS radiosonde profiles were obtained twice a day at 00:00 and/or 09:00 and/or 12:00 UTC with a vertical resolution of 300 m and a mean maximum altitude of 23 km.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical profiles of temperature and horizontal wind with 100 m resolution reached the mean altitude of 23 km. Radiosonde data quality and accuracy are described in Chane Ming et al ( , 2007 and Ibrahim (2010), which used similar vertical profiles to characterize GWs in the UT/LS. At Ivato airport (389 m altitude), 40 GPS radiosonde profiles were obtained twice a day at 00:00 and/or 09:00 and/or 12:00 UTC with a vertical resolution of 300 m and a mean maximum altitude of 23 km.…”
Section: Methodsmentioning
confidence: 99%
“…This observation could be related to the increase in convective activity in the southwestern Indian Ocean (SWIO) basin during this period. It is well known that low-pressure and tropical cyclone systems are a source of low-frequency convective gravity waves in the SWIO basin (Chane-Ming et al, 2007Ibrahim et al, 2010). Based on a 10-season climatology investigation (1997/1998-2006/2007) obtained from GPS windsonde, Ibrahim et al (2010) showed a linear relationship between weekly gravity waves total energy density in the lower stratosphere and the activity of intense tropical cyclones in the SWIO basin.…”
Section: Statistical Analysis Of Temperature Inversion Layermentioning
confidence: 99%
“…Recently, Chane‐Ming et al [2010] revealed a clear correlation between the daily maximum surface wind speed and the total energy density of low frequency GWs produced by intense TCs Dina and Faxai in the upper troposphere (UT)/lower stratosphere (LS). Among others, a positive contribution in total energy density of about 30% in the LS was quantified above Tromelin during intense TC Dina as compared with climatology in austral summer [ Chane‐Ming et al , 2007].…”
Section: Introductionmentioning
confidence: 99%